Dekonstruksi ‘Adalah al-Shahābah Kepada Rekonstruksi Definisi Sahabat: Kajian Kritis mengenai Sahabat dalam Tinjauan Nās - Muhammad Tahir Alibe (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This article aims to examine the rules of al-Shahabah Kulluhum 'Udul based on the Qur'an and Hadith. Examine the arguments used to justify the rule. The results of the study indicate that the rule of al-Shahabah Kulluhum 'Udul is complicated to maintain because the description of the Qur'an and hadith about friends are different; there are so-called groups of believers, groups of hypocrites, and wicked people. So generalize that all fair is wrong. This rule is more accurately called a dogma than as a historical fact. This study uses a type of library research with a theological-historical approach, namely by using the doctrines of the Qur'an and Hadith about friends. Since the doctrine of al-Shahabah Kulluhum 'Udul cannot be defended, there are at least two things that need to be done; first, reconstructing the definition of a friend; second, rejecting the rule of 'is al-Shahābah Kulluhum 'Udul. The correct redefinition of companions is who SAW or met the Prophet in a state of faith or pretended to believe and died in such a state.